It has been known that phytoplasma inducing witches broom disease can infect various kind of leguminous plants in Indonesia, among others soybean. Information on the resistance of various kind of soybean varieties to the phytoplasma is still limited. Experiments were conducted to eveluate the resistance of ten soybean varieties/lines to the phytoplasma. The evaluation was carried out by inoculation method through Orosius argentatus Evans, with two days of acquisition feeding period, ten days lat - Asniwita Asniwita; Rusmilah Suseno; Sri Hendrastuti Hidayat; Budi Tjahjono (Buletin Hama dan Penyakit Tumbuhan, 1999)
It has been known that phytoplasma inducing witches broom disease can infect various kind of leguminous plants in Indonesia, among others soybean. Information on the resistance of various kind of soybean varieties to the phytoplasma is still limited. Experiments were conducted to eveluate the resistance of ten soybean varieties/lines to the phytoplasma. The evaluation was carried out by inoculation method through Orosius argentatus Evans, with two days of acquisition feeding period, ten days latent period and two days inoculation feeding period. Observation was conducted on the presence of phytoplasma, incubation period, symptom and number & weight of seed. The result indicated that line Malang 3474 was resistant, Sindiro and Sriono were tolerant, while the other tested varieties/lines, i.e. Galunggung, Orba, Ringgit, Wilis, Malang 2999, Malang 2805 and Sicinang were susceptible